To Begin Understanding Biotechnology - Madríz, Jorge (2004)
This essay presentss to a non-specialist audience in biotechnology concepts, definitions and opinions of prominent researchers and thinkers in this field, who will try to inform and educate about a subject in which there is no article that is easy to understand for the public, but which has a direct impact on their lives, in the development of their environment and poses new problems and responsibilities to all humanity.